Photolithography patterning process and resists used therein
By using perovskite materials and inorganic core-shell nanoparticles, an efficient resist composition was designed, which solved the problem of difficulty in both resist performance in EUV lithography, and achieved high resolution, low roughness and high The effect of sensitivity.
Patent Information
- Application Number
- CN202110243439.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2015-04-24
- Filing Date
- 2015-12-01
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2035-12-01
AI Technical Summary
In the existing EUV lithography technology, the resist composition is difficult to balance between resolution, line width roughness and sensitivity, and the manufacturing process may require high temperature or non-radiation processes, resulting in inefficiency.
Using perovskite materials as the basis of the resist composition, a high-efficiency resist composition is designed by selecting appropriate chemical formulas and components, and inorganic core-shell nanoparticles are synthesized at room temperature to improve corrosion resistance. performance of agent.
It is achieved to improve the resolution of the resist, reduce linewidth roughness and increase sensitivity in EUV lithography, while simplifying the manufacturing process and reducing costs and energy consumption.
Smart Images

Figure CN113009782B_ABST
Abstract
Description
[0001] This application is a divisional application of a Chinese invention patent application with an application date of December 1, 2015, application number 201580070512.8, and invention name “Photolithography patterning process and resist used therein”.
[0002] CROSS-REFERENCE TO RELATED APPLICATIONS
[0003] This application claims priority to EP application 14200085.0 filed on December 23, 2014 and EP application 15165023.1 filed on April 24, 2015, both of which are incorporated herein by reference in their entirety. Technical Field
[0004] The present invention relates to the use of a particular resist composition comprising a perovskite material for lithographic purposes, and a patterning method or process using such a resist composition. The present invention also relates to a resist composition comprising inorganic particles such as core-shell nanoparticles. The present invention further relates to a positive resist composition. Background Art
[0005] In photolithography, a desired pattern is applied to a substrate (usually to a target portion of the substrate). A photolithographic apparatus may be used, for example, in the manufacture of an integrated circuit (IC). In this example, a patterning device, alternatively referred to as a mask or reticle, may be used to generate a circuit pattern to be formed on a separate layer of the IC. The pattern may be transferred to a target portion on a substrate (e.g., a silicon wafer). The transfer of the pattern is typically by imaging onto a radiation-sensitive material layer, usually referred to as a resist, disposed on the substrate. In general, a single substrate will contain a network of adjacent target portions that are patterned one after the other.
[0006] Photolithography is widely recognized as one of the key steps in the manufacture of ICs and other devices and / or structures. However, as the size of features made using photolithography becomes smaller and smaller, photolithography is becoming a more critical factor for enabling the manufacture of miniature ICs or other devices and / or structures. A theoretical estimate of the limit of pattern printing is shown in equation (1):
[0007]
[0008] where λ is the wavelength of the radiation used, NA is the numerical aperture of the projection system used to print the pattern, k1 is a process-dependent adjustment factor (also called the Rayleigh constant), and CD is the feature size (or critical dimension) of the printed features. From equation (1), it follows that a reduction in the minimum printable size of a feature can be obtained in three ways: by shortening the exposure wavelength λ, by increasing the numerical aperture NA, or by reducing the value of k1.
[0009] In order to shorten the exposure wavelength and thus reduce the minimum printable size, it has been proposed to use an extreme ultraviolet (EUV) radiation source. EUV radiation is electromagnetic radiation with a wavelength in the range of 5nm to 20nm (for example, in the range of 13nm to 14nm). Such radiation is sometimes referred to as soft x-ray radiation. EUV radiation can be generated using plasma. A radiation system for generating EUV radiation may include a laser for exciting a fuel to provide a plasma, and a source collector module for containing the plasma. Plasma can be generated, for example, by directing a laser beam at a fuel such as a flow of particles of a suitable material (for example, tin) or a suitable gas or vapor (such as Xe gas or Li vapor). Such a radiation system is typically referred to as a laser produced plasma (LPP) source. Alternative sources include discharge plasma sources, or sources based on synchrotron radiation provided by an electron storage ring.
[0010] A particular challenge for the development of commercial EUV lithography is the formulation of radiation-sensitive resist compositions that will achieve high-resolution patterns projected by EUV optical systems in etch-resistant materials. Photoresists typically convert optical contrast into chemical contrast that can be developed to transfer patterns to the resist. For EUV lithography, the most advanced photoresists are currently chemically amplified photoresists (CARs) that compromise between resolution, line width roughness, and sensitivity. Due to the interdependence of these properties, modifications made on photoresist compositions to improve one of these properties typically result in degradation of one or both of the other properties. Another challenge is that the manufacture of such resist compositions may require synthesis steps at high temperatures, or may require the use of non-radiative processes to reduce electron-ligand efficiency.
[0011] During exposure, EUV photons are absorbed by the photoresist. Due to the high energy of EUV photons, absorption by the nuclear level of atoms is the dominant mechanism and therefore the atomic composition and density of the photoresist are the main driving forces for EUV absorption. Current organic photoresists all have similar EUV absorption coefficients, which result in approximately 25% EUV absorption, with the remainder of the photons incident on the wafer being mostly wasted. Total absorption is limited by sidewall angle considerations related to the absorptivity and the thickness of the resist layer.
[0012] During exposure, photoacid is generated from the photoacid generator (PAG), which further catalyzes the deprotection reaction in the post-exposure bake step applied to the photoresist. When a certain amount of deprotection ratio is reached, this portion of the photoresist can be dissolved away in the development step. In this way, a resist pattern with a certain size and roughness is formed.
[0013] Diffusion during post-exposure baking is generally random in all directions and forms a significant portion of the total blur together with secondary electron blur. It would be beneficial to limit the horizontal diffusion of the acid and promote vertical acid diffusion (in the z direction). The resist would ideally show limited blurring in the xy direction and dominant blurring in the z direction, and the photoacids that diffuse along the resist height (z direction) would deprotect larger volumes than when they diffuse isotropically.
[0014] Current organic-based chemically amplified resists generally do not meet all requirements such as dose, roughness, and resolution requirements for sub-16 nm features for EUV lithography. The generally low absorption of CARs results in limited sensitivity of the resist, leading to high doses required to mitigate the effects of photon shot noise at small pitches.
[0015] Increasing the total absorption would be beneficial in order to use EUV photons more efficiently. However, increasing the total absorption while keeping the resist profile at about 90 degrees remains a challenge. If a higher absorbing material is used, the total resist film thickness needs to be adjusted / reduced accordingly, at which point etch resistance becomes an issue. Another problem is pattern damage, which limits the achievement of high resolution and high aspect ratio materials. Another cause of pattern damage is poor adhesion of the photoresist to the substrate and low mechanical strength of the resist material. There is a need for new resist compositions that address one or more of the above problems. Summary of the invention
[0016] According to one aspect of the present invention, there is provided a resist composition comprising a perovskite material. The perovskite material has a structure having a chemical formula selected from ABX3, A2BX4 or ABX4, wherein A is a compound containing an NH3 group, B is a metal and X is a halide component. The resist composition may also include a mixture of such perovskite materials.
[0017] In an embodiment, the resist composition includes a perovskite material selected from one or more of the following: a) mixed halogen perovskite material, b) mixed metal perovskite material, and c) mixed organic ligand perovskite material.
[0018] In an embodiment, compound A is selected from C X H X+2 NH3、C6H5C x H 2x NH3、NH3C x H 2x The group consisting of NH3 and NH2CHNH3 and combinations thereof, wherein x is an integer in the range from 1 to 5.
[0019] In another embodiment, B is selected from Pb2+ Sn 2+ , Cu 2+ , Mn 2+ , Fe 2+ and mixed metals (or mixed anions) constitute the group of metals.
[0020] In yet another embodiment, X is a halide component selected from the group consisting of I, Br, F, and Cl.
[0021] In a further embodiment, the resist composition includes a perovskite material comprising: a methylammonium lead halide perovskite having a molecular formula of CH3NH3PbX3, and / or an ethylammonium lead halide perovskite having a molecular formula of CH3NH3PbX3, wherein the halide component is selected from I, Br or Cl. Examples of suitable perovskite materials are CH3NH3PbI3, CH3CH2NH3PbI3, CH3NH3PbBr3, CH3NH3PbI3, CH3NH3PbI2Br, CH3NH3Pb(I 1-X Br x )3. CH3NH3PbI2Cl, NH2=CHNH3 + Lead-based materials, and CH3NH3PbI (3-X) Cl x ; where x is an integer in the range from 1 to 5.
[0022] In an embodiment, the resist composition includes from about 1 wt % to about 98 wt % of the perovskite material as described above. The resist composition may optionally further include at least one of a second resin compound, a solvent, a surfactant or other additives.
[0023] In an embodiment, there is provided a pattern forming method comprising the steps of applying a resist composition to a substrate to form a coating, baking the coating, exposing the coating to high energy radiation, and developing the exposed coating in a developer. The exposure step can be performed, for example, by immersion lithography, by electron beam lithography, by imprint lithography, or by EUV lithography using EUV radiation having a wavelength of 3 nm to 20 nm.
[0024] In another embodiment, there is provided a method for producing a resist composition as described in the above embodiments, wherein the perovskite material and / or the resist composition is synthesized at room temperature. In addition, in the manufacture of the resist composition, it is advantageous to use anhydrous starting materials in a dry enclosure such as a drying oven.
[0025] In an embodiment, a perovskite material having a structure with a chemical formula selected from ABX3, A2BX4, ABX4, or a mixture of such perovskite materials is used in a photolithography process for manufacturing integrated circuits, wherein A is a compound containing an NH3 group, B is a metal and X is a halide component.
[0026] In another embodiment according to the present invention, there is provided a resist composition comprising an inorganic core-shell nanoparticle, the nanoparticle comprising a first material forming a core of the nanoparticle and a second material forming a shell around the core,
[0027] Wherein the second material has an energy bandgap greater than the energy bandgap of the first material. The first (core) material may for example be CdSe and the second (shell) material may for example be ZnS. In an embodiment, the nanoparticles are core-shell nanoparticles comprising a material selected from CdS / ZnS, CdSe / CdS and InAs / CdSe.
[0028] In another embodiment according to the present invention, there is provided a kind of resist composition, including inorganic core-shell nanoparticles, the nanoparticles include the first material forming the core of the nanoparticles and the second material forming the shell around the core, wherein the absolute band gap position of the second material is arranged to shield one of the electrons or holes as charge carriers and attract another charge carrier. The shell around the core therefore ensures better charge carrier separation in the nanoparticles. The first (core) material can be, for example, ZnTe and the second (shell) material can be CdSe.
[0029] In an embodiment, such a resist composition is characterized in that the band gap of the first material is higher than the band gap of the second material, so that the absolute band gap positions of the first and second materials are different on an absolute energy scale, thereby causing a spatial separation of electrons and holes, wherein the holes are located closer to the surface of the core-shell nanoparticles. In such a resist composition, the main excitation mechanism upon irradiation with EUV is linear single-photon type absorption (activation).
[0030] In another embodiment according to the present invention, there is provided a resist composition comprising inorganic nanoparticles, the inorganic nanoparticles comprising a material having an overall band gap of less than 3.5 eV. Such a resist composition can have a material of inorganic particles selected from, for example, ZnO, WO3, CdS, CdSe, GaP, InAs, InP, GaAs, CdTe, GaSb, InN, InSb, ZnSe and ZnTe.
[0031] In another embodiment according to the present invention, there is provided a positive photoresist composition comprising a first group of inorganic nanoparticles A and a second group of inorganic nanoparticles B, wherein the nanoparticles A are provided with photons on an electron-sensitive ligand, the electron-sensitive ligand comprising a chemical group having a first side attached to the nanoparticles A and a second side arranged to prevent cross-linking of the nanoparticles A and B at room temperature, and the chemical group is removable at a temperature above room temperature; wherein the nanoparticles B are provided with ligands having weakly-bonded chemical groups, the weakly-bonded chemical groups being arranged to be replaced by photons on the electron-sensitive ligand attached to the nanoparticles A at a temperature above room temperature, thereby providing cross-linking of the nanoparticles A and B; and wherein the photons on the electron-sensitive ligand are arranged to dissociate from the nanoparticles A during photolithographic exposure with photons or low-energy photons. The amount of the inorganic nanoparticles A can be, for example, about half of the total amount of the inorganic nanoparticles A and B.
[0032] In an embodiment, the part is for example combined with the metal atom of the nanoparticle shell by making the inorganic shell react directly with the desired part. In some instances, the part can also play the role of a surfactant, to keep the core-shell nanoparticle well dispersed in the solution. The nanoparticle can have an inorganic core, an inorganic shell and an organic surface provided by the part. A type of charge carrier produced in the core can be transferred to the shell, and then they are transferred from the shell to the part that will chemically react.
[0033] Nanoparticle A may have a hydrogen selective bridge at its surface, such as a =H weak bonding group, while nanoparticle B may have a complementary ligand group that cross-links with the A-type ligand (or vice versa) via hydrogen bonding.
[0034] The ligands can be composed of groups such as COO-, phosphonate groups -PO3 - , sulfonyl group -SO3 - , oxalate group (COO)2 2- 、Carbonate-based CO2 3- , azide group N3- and nitrite group -NO2 - Nanoparticles comprising photons on electron sensitive ligands as described above that can dissociate during photolithographic exposure will thus provide free nanoparticles that can be removed by resist developers.
[0035] In an embodiment according to the present invention, there is provided a method for preparing a positive photoresist composition, the resist composition comprising a first group of inorganic nanoparticles A and a second group of inorganic nanoparticles B, the method comprising the following steps:
[0036] A first group of nanoparticles A is provided with photons on an electron sensitive ligand, the electron sensitive ligand comprising a chemical group having a first side attached to nanoparticle A and a second side arranged to prevent cross-linking of nanoparticles A and B at room temperature, the chemical group being removable at a temperature above room temperature; and wherein the photons on the electron sensitive ligand are arranged to dissociate from nanoparticle A during photolithographic exposure with photons or low energy photons; and a second group of nanoparticles B is provided with ligands having weakly bonded chemical groups arranged to be displaceable by the second side of the chemical group at a temperature above room temperature by photons attached to the electron sensitive ligand of nanoparticle A. A further step may be to apply a baking temperature to the positive photoresist to allow cross-linking of nanoparticles A and B. Another further step in the above method of making a positive photoresist composition is to expose the cross-linked positive photoresist composition with photons or low-energy photons, so that the photons on the electron-sensitive ligand dissociate from the nanoparticles A during the photolithographic exposure, thereby leaving free nanoparticles in the exposed areas of the positive photoresist.
[0037] In another embodiment, there is provided a resist composition comprising: a substance comprising a self-assembling molecule having a self-assembling body group for self-assembly to a substrate material, a layer of the substrate contacting the resist composition, the self-assembling molecule further having a passive capping group different from the self-assembling body group, the passive capping group becoming an active capping group when irradiated with photolithographic radiation; and an inorganic nanoparticle configured not to chemically bind to the passive capping group or the self-assembling body group of the self-assembling molecule, wherein the inorganic nanoparticle is configured to chemically bind to the active capping group of the self-assembling molecule. Such a resist composition has anisotropic acid diffusion or no acid diffusion properties.
[0038] The resist composition can have the multilayer of inorganic nanoparticles.The inorganic nanoparticles can be metal nanoparticles.In one embodiment, the inorganic nanoparticles are rod-shaped elongated particles that can be oriented in the direction of the substrate that the layer of the inorganic resist composition contacts with it perpendicularly.In such a situation, the catalyst diffusion can be oriented substantially in the direction of the substrate that the layer of the inorganic resist composition contacts with it perpendicularly, thus providing a resist layer with anisotropic fuzziness.
[0039] Passive end-capping groups are C end-capping groups that can be converted into active end-capping groups when exposed to photolithographic radiation beams, such as -CH3 end-capping groups. The active end-capping groups of the self-assembled monolayer molecules can be selected from -COOH, -SH or -N3 groups. The active end-capping groups of the self-assembled monolayer molecules can alternatively be PAG end-capping groups including one or more of the groups CFSO3-, TPS or SbF6. If the passive end-capping group is a PAG group including CFSO3- and TPS groups, then the passive end-capping group is activated by the disengagement of the TPS group when irradiated with photolithographic radiation, so that the CFSO3- group forms an active end-capping group.
[0040] In one embodiment, the reactive end-capping groups of the self-assembled monolayer molecules are -N3 azide groups and the inorganic nanoparticles include FePt.
[0041] In another embodiment, the surface of the inorganic nanoparticles is protected with a surfactant having C=C endcaps linked to the inorganic nanoparticles via epoxy crosslinker groups.
[0042] Upon irradiation with photolithographic radiation such as EUV radiation, the passive capping groups are transformed into active capping groups such that the inorganic particles attached to the self-assembled molecules become removable at the irradiated areas of the resist layer, while the inorganic particles from the unirradiated areas remain bonded in the resist layer.
[0043] In another embodiment, there is provided a substrate coated with the resist composition according to any one of the embodiments described above.
[0044] Specific examples and variations thereof are further described below to help understand the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0045] Embodiments of the invention will now be described, by way of example only, with reference to the accompanying schematic drawings, and in which:
[0046] Figure 1 schematically depicts functional elements of a lithographic apparatus for use in embodiments of the present invention;
[0047] Figure 2 yes Figure 1 A more detailed view of the device. DETAILED DESCRIPTION
[0048] Figure 1A lithographic apparatus 100 for use in an embodiment of a device manufacturing process according to an embodiment of the invention is schematically depicted. The apparatus comprises: a source collector module SO; an illumination system (illuminator) IL configured to condition a radiation beam B (e.g., EUV radiation); a support structure (e.g., a mask stage) MT configured to support a patterning device (e.g., a mask or reticle) MA and connected to a first positioner PM configured to accurately position the patterning device; a substrate stage (e.g., a wafer stage) WT configured to hold a substrate (e.g., a wafer coated with an anti-agent) W and connected to a second positioner PW configured to accurately position the substrate; and a projection system (e.g., a reflective projection system) PS configured to project a pattern imparted to the radiation beam B by the patterning device MA onto a target portion C (e.g., comprising one or more dies) of the substrate W.
[0049] The illumination system may include various types of optical components, such as refractive, reflective, magnetic, electromagnetic, electrostatic or other types of optical components, or any combination thereof, for directing, shaping or controlling the radiation.
[0050] The support structure MT holds the patterning device MA in a manner that depends on the orientation of the patterning device, the design of the lithographic apparatus, and other conditions such as, for example, whether the patterning device is held in a vacuum environment. The support structure can use mechanical, vacuum, electromagnetic or other clamping techniques to hold the patterning device. The support structure can be, for example, a frame or a stage, which can be fixed or movable as required. The support structure can ensure that the patterning device is in a desired position, for example relative to a projection system.
[0051] The term "patterning device" should be broadly interpreted as referring to any device that can be used to impart a radiation beam with a pattern in its cross-section so as to create a pattern in a target portion of a substrate. The pattern imparted to the radiation beam may correspond to a particular functional layer in a device such as an integrated circuit being created in the target portion.
[0052] The patterning device may be transmissive or reflective. Examples of patterning devices include masks, programmable mirror arrays, and programmable LCD panels. Masks are well known in lithography and include mask types such as binary, alternating phase shift, and attenuated phase shift, as well as various hybrid mask types. An example of a programmable mirror array employs a matrix arrangement of small mirrors, each of which can be individually tilted to reflect an incoming radiation beam in different directions. The tilted mirrors impart a pattern on the radiation beam that is reflected by the mirror array.
[0053] The projection system, like the illumination system, may include various types of optical components, such as refractive, reflective, magnetic, electromagnetic, electrostatic or other types of optical components, or any combination thereof, depending on the exposure radiation being used or other factors such as the use of a vacuum. For EUV radiation it may be desirable to use a vacuum, as other gases would absorb too much radiation. Therefore a vacuum environment may be provided to the overall beam path with the help of a vacuum wall and a vacuum pump.
[0054] As depicted here, the device is reflective (eg, employing a reflective mask).
[0055] The lithographic apparatus may be of a type having two (dual stage) or more substrate tables (and / or two or more mask tables). In such a "multi-stage" machine the additional tables may be used in parallel, or preparatory steps may be performed on one or more tables while one or more other tables are being used for exposure.
[0056] See also Figure 1 , the illuminator IL receives a beam of extreme ultraviolet radiation from a source collector module SO. Methods for generating EUV light include, but are not necessarily limited to, utilizing one or more emission lines in the EUV range to convert a material into a plasma state having at least one element, such as xenon, lithium, or tin. In one such method, commonly referred to as laser produced plasma ("LPP"), the desired plasma may be generated by irradiating a fuel, such as a droplet, stream, or cluster of material having the desired line-emitting element, with a laser beam. The source collector module SO may be a laser beam that provides a laser beam for exciting the fuel. Figure 1 The laser is a part of an EUV radiation system of a laser not shown in FIG. The generated plasma emits output radiation, such as EUV radiation, which is collected using a radiation collector arranged in a source collector module. The laser and the source collector module may be separate entities, for example when a CO2 laser is used to provide the laser beam for fuel excitation.
[0057] In such cases, the laser is not considered to form part of the lithographic apparatus and the radiation beam is delivered from the laser to the source collector module with the aid of a beam delivery system comprising, for example, suitable guiding mirrors and / or a beam expander. In other cases, the source may be an integral part of the source collector module, for example when the source is a discharge produced plasma EUV generator, often referred to as a DPP source.
[0058] The illuminator IL may include an adjuster for adjusting the angular intensity distribution of the radiation beam. In general, at least the outer radial extent and / or the inner radial extent (often referred to as σouter and σinner, respectively) of the intensity distribution in a pupil plane of the illuminator may be adjusted. In addition, the illuminator IL may include various other components such as a facet field and a pupil mirror arrangement. The illuminator may be used to adjust the radiation beam to have a desired uniformity and intensity distribution in its cross-section.
[0059] The radiation beam B is incident on a patterning device (e.g., mask) MA held on a support structure (e.g., mask table) MT and is patterned by the patterning device. After reflection from the patterning device (e.g., mask) MA, the radiation beam B passes through a projection system PS, which focuses the beam onto a target portion C of the substrate W. With the help of a second positioner PW and a position sensor PS2 (e.g., an interferometer device, a linear encoder or a capacitive sensor), the substrate table WT can be accurately moved, for example in order to position different target portions C in the path of the radiation beam B. Similarly, a first positioner PM and a further position sensor PS1 can be used to accurately position the patterning device (e.g., mask) MA relative to the path of the radiation beam B. The patterning device (e.g., mask) MA and the substrate W can be aligned using the mask alignment marks M1, M2 and the substrate alignment marks P1, P2.
[0060] Figure 2 The device 100 including a source collector module SO, an illumination system IL and a projection system PS is shown in more detail. The source collector module SO is constructed and arranged so that a vacuum environment can be maintained in the closed structure 220 of the source collector module SO. The EUV radiation emitting plasma 210 can be formed by a discharge generating plasma source. EUV radiation can be generated by a gas or vapor, such as Xe gas, Li vapor or Sn vapor, in which a very hot plasma 210 is generated to emit radiation in the EUV range of the electromagnetic spectrum. The very hot plasma 210 is generated by, for example, a discharge that causes an at least partially ionized plasma. For efficient generation of radiation, a partial pressure of, for example, 10 Pa of Xe, Li, Sn vapor or any other suitable gas or vapor may be required. In an embodiment, an excited tin (Sn) plasma is provided to generate EUV radiation.
[0061] The radiation emitted by the hot plasma 210 is transferred from the source chamber 211 into the collector chamber 212 via an optional gas barrier or contaminant trap 230 (also referred to as a contaminant barrier or foil trap in some cases) positioned in or behind an opening in the source chamber 211. The contaminant trap 230 may include a channel structure. The contaminant trap 230 may also include a gas barrier or a combination of a gas barrier and a channel structure. The contaminant trap or contaminant barrier 230 further indicated herein includes at least a channel structure as known in the art.
[0062] The collector chamber 211 may include a radiation collector CO, which may be a so-called grazing incidence collector. The radiation collector CO has an upstream radiation collector side 251 and a downstream radiation collector side 252. Radiation traversing the collector CO may be reflected off the grating spectral filter 240 to be focused in a virtual source point IF. The virtual source point IF is often referred to as an intermediate focus, and the source collector module is arranged so that the intermediate focus IF is located at or near an opening 221 in the enclosure 220. The virtual source point IF is an image of the radiation emitting plasma 210.
[0063] The radiation then traverses an illumination system IL which may include a faceted field mirror arrangement 22 and a faceted pupil mirror arrangement 24 arranged to provide a desired angular distribution of the radiation beam 21 at the patterning device MA and a desired uniformity of radiation intensity at the patterning device MA. When the radiation beam 21 is reflected at the patterning device MA held by the support structure MT, a patterned light beam 26 is formed and the patterned light beam 26 is imaged by the projection system PS via reflective elements 28, 30 onto a substrate W held by a wafer stage or substrate table WT.
[0064] In general, there may be more elements in the illumination optics unit IL and the projection system PS than shown. A grating spectral filter 240 may optionally be present, depending on the type of lithographic apparatus. Furthermore, there may be more mirrors than shown in the figure, for example Figure 2 Compared to what is shown in FIG. 1 , there may be 1 to 6 additional reflective elements present in the projection system PS.
[0065] like Figure 2 The collector optics CO illustrated in FIG. 1 is depicted as a nested collector with grazing incidence reflectors 253, 254 and 255, just as an example of a collector (or collector mirror). The grazing incidence reflectors 253, 254 and 255 are arranged axially symmetrically around the optical axis O, and this type of collector optics CO is typically used in combination with a discharge produced plasma source, often called a DPP source.
[0066] Alternatively, the source collector module SO can be part of an LPP radiation system using a near normal incidence collector optical device (not shown). In an LPP system, the laser is arranged to deposit laser energy into the fuel material, thereby generating a highly ionized plasma with an electron temperature of tens of eV. The radiation with energy generated during the deexcitation and recombination of these ions is emitted from the plasma, collected by the near normal incidence collector optical device and focused onto the opening 221 in the closed structure 220.
[0067] Device manufacturing process
[0068] A typical patterning process as part of a method for manufacturing a device typically uses Figure 1 and Figure 2 An apparatus for transferring a pattern from a patterning device M to a radiation-sensitive resist composition (referred to as “resist”) on a substrate W.
[0069] In a patterning process using resists in order to manufacture items such as ICs, there may be several manufacturing steps, such as the following seven steps (S0 to S7) described below:
[0070] S0: Prepare a substrate W, which may be, for example, a silicon wafer.
[0071] S1 (Coating): The resist solution is spin-coated to form a very thin uniform layer on the substrate W. The resist layer may be baked at a low temperature to evaporate the residual solvent.
[0072] S2 (Exposure): A latent image is formed in the resist layer by exposure to EUV using the lithography apparatus 100 and a suitable patterning device M.
[0073] S3 (Develop & Etch): In the case of a "positive" resist, the exposed areas of the resist are removed by washing with an appropriate solvent. In the case of a "negative" resist, the unexposed areas are removed. This step is combined with or followed by a processing step through the resist pattern to the substrate. The term "etching" in the drawings is used as an example only. The processing steps may include wet or dry etching, stripping, doping, etc. By whatever process, the applied pattern becomes reflected in the addition, removal or modification of material on the substrate. The diagram shows the removal of material, ready for the deposition step S5.
[0074] S4 (stripping): removing the remaining resist from the patterned substrate W.
[0075] S5 (Deposition): Different substances are deposited to fill the pattern of the substrate W.
[0076] S6 (Polishing): Excess materials are removed from the surface of the wafer W by polishing, leaving only the desired pattern within the wafer W.
[0077] Steps S1 to S6 are repeated with different patterns and different processing steps to produce functional features with desired patterns in different layers above and below the original surface of the substrate W until the final multilayer product is delivered (step S7). The product is typically but not necessarily a semiconductor device such as an integrated circuit.
[0078] As discussed, it will be appreciated by those skilled in the art that steps S4 and S6 are merely one example of a process that can be applied in a pattern determined by the exposed resist. Many different types of steps can or will be used at different stages of production. For example, the resist can be used to control the modification of the underlying material rather than etching it away. The modification can be, for example, oxidation, doping, such as by diffusion or ion implantation. A new layer of material can be deposited on top of the substrate. In many processes, the photoresist is merely an intermediate stage in producing a so-called "hard mask" that reproduces the exposed pattern in a different material. The hard mask is then used to control the process steps of etching or modifying the underlying material with the desired pattern but not controlled by the photoresist itself. Therefore, depending on the sequence of patterns and layers sought to be produced and the intermediate steps required to build the finished device, the above-mentioned process can be changed; some steps are combined and / or removed and some additional steps are added.
[0079] EUV radiation is absorbed by the resist composition and generates photoelectrons and secondary electrons. The secondary electrons cause some random exposure, which is superimposed on the optical image applied by the EUV source on the resist. This in turn leads to a loss of resolution, observable line edge roughness and line width variations, which are known as "blurring" phenomena. If the resist is to deliver the high resolution expected in EUV lithography, this blurring needs to be controlled.
[0080] Pattern destruction occurs when the physical properties of the resist composition cannot counteract the capillary or repulsive forces exerted on the pattern to a sufficient extent during the drying of the rinse solution. High rigidity or strength of the coating formed by such a resist composition is therefore desirable, as is a reduced aspect ratio of the features of the pattern.
[0081] Other process parameters that lead to variations in the resolution capability of the resist are, for example, etch resistance and selectivity, quantum yield, bake time and temperature, exposure time and source output, aerial image focus, and development time and temperature. The ability of a particular resist to allow for some degree of variation in these particular parameters is of course highly desirable to be able to operate within specified tolerances.
[0082] Organic resist
[0083] Traditional organic resists for DUV and EUV lithography are chemically amplified resists (CARs) such as poly(butylene-1-sulfone) and poly(α-methyl chloroacrylate-co-α-methylstyrene). CAR materials consist of a composite polymer mixture. When excited with EUV, photons are absorbed by the polymer and the chemical components present on the resin release acid groups when the radiation is exposed. With the secondary electrons, the photoacid generator (PAG) is excited. When excited, the PAG decomposes and diffuses during the post-exposure baking step, and it can catalyze the unblocking reaction that changes the resist from hydrophobic to hydrophilic. These acid groups can therefore render the surrounding polymer soluble in the developer. Acid diffusion helps increase the sensitivity and yield of the resist, and also helps limit the line edge roughness attributed to shot noise statistics. However, the acid diffusion length itself is a potential limiting factor. In addition, too much diffusion may reduce the chemical contrast, which may again lead to more roughness. Also, CAR materials are based on carbon with a low cross-section that utilizes EUV. This results in a too transparent resist which requires a high dose, ie a high EUV source power, which is undesirable.
[0084] Inorganic resist
[0085] In order to overcome the high absorption rate specific to CAR, inorganic resist compositions, such as various metal oxides, have been proposed in the art. Inorganic resists can present increased resistance to blurring and resistance to pattern destruction due to their strength. Stowers et al., published in SPIE Proceedings Volume 7969, Pages 796915-796915-l1 (2011), "Direct Patterning Inorganic Hard Mask for EUV Lithography" describes the use of hafnium sulfate oxide combined into a peroxide complexing solvent to form a negative resist. Exposure to EUV results in the generation of secondary electrons that destroy the bonding of peroxide groups. Active metal sites are thus generated, and their reactions produce crosslinking and condensation regions.
[0086] The specific category of inorganic resist is based on inorganic nanoparticles. Most of these materials can be synthesized at room temperature. However, such synthesis usually results in inefficient nanocrystals because nanocrystals are full of defects. In the high temperature synthesis of nanocrystals, defects can be annealed, but it is generally costly and not desirable for large-scale production. Low efficiency means that there is a non-radiative path mode (undesirable process) that takes away the energy of the excited one by means of phonons instead of transferring it to the ligand (desirable process).
[0087] The key steps in organic nanoparticle resists are:
[0088] - Absorption of photons (atoms);
[0089] - Generation of electrons having the kinetic energy to generate an excited valence band electron and a corresponding hole in a bound state of an electron-hole pair (exciton);
[0090] - transfer of excitation energy (by using either electrons or holes in a reaction) to molecules at the surface of the nanoparticles (called ligands);
[0091] - Chemical changes in the ligands cause the nanoparticles to aggregate or become insoluble;
[0092] - Dissolution of irradiated nanoparticles (positive) or more often non-irradiated (negative).
[0093] All of these processes need to be sufficiently efficient in order to obtain a durable resist. Once an excitation (i.e., a bound electron-hole pair) is generated, its energy may be lost through several processes:
[0094] - radiative decay by emission of photons (typical time 1 to 10 nanoseconds);
[0095] - non-radiative decay (typically picoseconds) by multiple phonon emission or by trapping on defects; and / or
[0096] - Capture of electrons or holes on the ligand (typical time picoseconds).
[0097] It is therefore highly desirable to provide resist compositions that can meet the requirements of EUV lithography.
[0098] Perovskite-type organic-inorganic hybrid materials are crystalline systems in which both inorganic and organic structural elements coexist in a single phase. Hybrid inorganic-organic materials are defined as compounds containing inorganic and organic components as integral parts of a network with infinite bonding connectivity in at least one dimension.
[0099] Nanocrystalline organometallic halide perovskite materials are a class of metal-organic frameworks of hybrid inorganic-organic materials for solar cells with high efficiency. Organometallic perovskites, for example, include mixed anions of two or more different anions selected from halide anions. Perovskite originally referred to minerals containing CaTiO3, and the term was later extended to cover a class of compounds having a crystal structure with the same general chemical formula ABX3 as CaTiO3, where A and B are cations of different sizes and X is an anion. Substituting oxide perovskite species (X1 / 4O), halide perovskite compounds (X1 / 4Cl, Br, F or I) were found to be characterized by excellent light harvesting (absorption) and electronic conduction properties and suitable for use as photovoltaic materials.
[0100] As used herein, the term "mixed anion" refers to a compound comprising at least two different anions. The term "halide" refers to an anion of a Group 7 element (i.e., a halogen). Typically, a halide refers to a fluoride anion, a chloride anion, a bromide anion, an iodide anion, or an astatide anion.
[0101] Hybrid organic-inorganic lead halide perovskites can accumulate the functions of light absorption, n-type conductivity and p-type conductivity. Perovskites absorb light and generate electron-hole pairs in the material. Among the lead halide perovskites, methylammonium lead halide perovskite absorbers are currently attracting increasing interest in the field of solar cells due to their ease of fabrication and performance.
[0102] It is now proposed to use nanocrystalline materials based on perovskites (or their mixtures) as the core of EUV inorganic resists for several reasons, such as having a bandgap structure just like semiconductors and having a long radiation decay rate at high luminescence quantum efficiency, and the advantage is that such materials can be synthesized using room temperature synthesis.
[0103] Although luminescence is undesirable for EUV resists, it is believed that having a core with a high radiative decay rate is very beneficial. The radiative decay rate is typically much slower (tens of nanoseconds) than the capture rate (picoseconds). When using ligands that can capture electrons or holes, this is believed to occur very efficiently, for example much more efficiently than when the core exhibits a high non-radiative process.
[0104] The perovskite resist composition according to the present invention comprises a material having a perovskite or perovskite-like crystal structure having a general chemical formula of one of ABX3, A2BX4, ABX4 or a mixture thereof (hereinafter referred to as a perovskite material). Herein, B is a metal selected from the following list, for example: B = Pb 2+ Sn 2+ , Cu 2+ , Mn 2+ , Fe 2+ ; Ca, Sr, Cd, Ni<2+>, Co<2+>, Pd<2+>, Ge<2+>, Yb<2+> and Eu<2+>; X is a halide selected from the following list, for example: X=I, Br, F and Cl; and A is an ammonium organic cation selected from the following list, for example: A=C X H X+2 NH3、C6H5C x H 2x NH3、NH3C x H 2x NH3 and NH2=CHNH3 +(formamide), wherein x is an integer in the range of from 1 to 5 (more preferably in the range of from 1 to 4). Other suitable compounds are naphthyl compounds (that is, having a diphenyl ring), or compounds with an F tail connected to a ring. In a word, A is a compound with at least one NH3 group. Such organic-inorganic hybrid materials can adopt the 3D or quasi-2D structure of the inorganic part, which depends on the connectivity between the octahedron. The hydrogen bond derived from NH3 group can facilitate the self-assembly of, for example, the material.
[0105] Preferably, the perovskite resin composition according to the present invention comprises methylammonium lead halide perovskite CH3NH3PbX3 or ethylammonium lead halide perovskite CH3NH3PbX3 having a halide component selected from I, Br, Cl. Examples of such materials are CH3NH3PbI3, CH3CH2NH3PbI3, CH3NH3PbBr3, CH3NH3PbI3, CH3NH3PbI2Br, CH3NH3Pb(I (1-x) Br x )3, CH3NH3PbI2Cl, and CH3NH3PbI (3-x) Cl x .
[0106] According to an example of the present invention, the perovskite resist composition may include from about 1 wt % to about 98 wt % of the perovskite material. However, the resist composition may also be made entirely of the perovskite material without further additives.
[0107] The perovskite resist composition of the present invention can be made by any known technique. The perovskite material is grown or / and templated by a solution or evaporation assisted method under special conditions. High quality films can be obtained, for example, by single or multi-step spin coating under ambient conditions without annealing from a precursor solution or high temperature thermal evaporation or multi-step deposition methods. For example, the CH3CH2NH3PbI3 perovskite material can be deposited on a substrate or another resist layer by spin coating of an equimolar mixture of CH3CH2NH3I and Pbl2 in a γ-butyrolactone solution.
[0108] The interlayer separation and thickness of the inorganic layer can be controlled by the choice of the organic cation A. The inorganic layer of most layered perovskites consists of a single sheet of corner-sharing metal halide octahedra sandwiched by an organic cation layer.
[0109] The synthesis of perovskite nanocrystals is sensitive to ambient humidity, since the perovskite can gradually dissolve into a liquid electrolyte after irradiation for, e.g., 10 minutes. For this reason, anhydrous starting materials should be used in a dry box during the synthesis.
[0110] The perovskite resist composition is coated on the desired substrate using well known techniques such as spin coating etc. Deposited Thickness The thickness of the deposited layer is advantageously in the range from 10 nm to 100 nm and may be less than 50 nm or even less than 30 nm.
[0111] In another embodiment the resist composition comprises core-shell nanoparticles.
[0112] Electron-hole pairs generated in resists may lose energy through non-radiative decay produced by multiple phonon emissions. Such non-radiative processes can occur at the same rate as electron or hole capture processes that lead to desired chemical changes. Therefore, they are undesirable processes in resists. Reducing such non-radiative processes, especially in inorganic resists, would be beneficial.
[0113] The inventor proposes to reduce non-radiative process by using core-shell nanoparticles in this article.Core-shell nanoparticles are layered nanoparticles made of two materials (first material for core nanoparticles and second material for the shell around core).For inorganic resists based on such core-shell nanoparticles according to the present invention, it is preferred that the second material (that is, shell) has a larger energy band gap than the first material of core.In nanoparticles, both electrons and holes may be constrained (Bohr radius of both electrons and holes may be greater than nanoparticle diameter), causing delocalized electrons and holes on nanoparticles.Overcoating of nanoparticles with large bandgap shell material (second material) will have the following results: 1) formation of "energy wall" at the surface of nanoparticles, this surface energy wall will cause 2) passivation of defects present at the surface of nanoparticles.Process 1) and 2) described above will reduce the non-radiative energy loss of core-shell nanoparticles. It is also believed that despite the presence of an energy barrier for electrons and holes due to the shell material, tunneling of electrons and holes can still occur through the layer, i.e., the capture process is not or barely hindered by the energy barrier. An example of such a nanoparticle is a CdSe (ZnS) core-shell nanoparticle, with CdSe as the core and ZnS as the shell.
[0114] In summary, making EUV inorganic resists with core-shell nanoparticles will therefore reduce the fast non-radiative decay rate in the nanoparticles and thereby increase the capture efficiency of electrons or holes on the ligands, resulting in a lower dose required for the resist.
[0115] In another embodiment, the core-shell nanoparticles are made according to so-called Type II nanoparticles. In such a case, the absolute band gap position of the second (shell) material is chosen so that it screens one of the charge carriers (electrons or holes) while attracting the other charge carrier. An example of such a Type II core-shell nanoparticle is CdSe (ZnTe), where the first material (core) is ZnTe and the second material (shell) is CdSe.
[0116] Although the band gap of ZnTe is higher than that of CdSe, the absolute positions of the two materials are not the same (on the absolute energy scale). This results in a potential for the confinement of electrons in this case, while holes obtain energy by going to the ZnTe material. This results in a spatial separation of electrons and holes, wherein holes are positioned closer to the surface. This is beneficial if holes are charge carriers that need to be transferred to nanocrystals. It is believed that more efficient transfer results in lower doses of resist.
[0117] In another embodiment, a resist composition is provided that includes a resist material having an overall energy gap of less than 3.5 eV.
[0118] A characteristic parameter for CAR is the so-called fuzziness, which is a measure of the length spanned by the photogenerated acid in the post-exposure bake step to diffuse and react in the resist. In such a diffusion-reaction process, the resist polymer is chemically altered by the catalytic reaction of the diffused acid. This can be considered a key factor in making low-dose CAR, where not every resist molecule needs to be excited, but only the catalyst needs to be activated.
[0119] However, CAR may still have limitations, for example in its radiation absorption. As an alternative, inorganic resist compositions have been proposed. However, there are other possible issues with inorganic resists, such as: a) secondary electron blur may need to be optimized, as the optimal resist blur for printing at minimum dose can typically account for about one-third of the critical dimension; and b) the number of electron-hole pairs generated per photon is preferably maximized.
[0120] In order to overcome the above-mentioned problems and limitations, the inventor proposes to use a high absorptivity material such as inorganic nanoparticles with a band gap less than 3.5eV in this article. The fuzzy characteristics in such resist materials are no longer driven by acid catalyst diffusion, but driven by the fuzziness or diffusion of the secondary electrons produced when photons are absorbed. For comparison, most of the known resist materials (such as ZfO2, HfO2, SnO2) have a band gap between 3.5eV and 6eV.
[0121] The choice of a smaller bandgap for this type of inorganic resist material can have two effects: i) secondary electron blurring can be increased; and / or ii) more secondary electrons are produced, whereby blurring and secondary electron yield are improved. The first effect comes from the fact that the energy of the electron determines its inelastic mean free path (MFP) in the resist material. If the bandgap energy is reduced, there may be a longer mean free path in the resist, and thus the blurring will be enlarged. On the other hand, the bandgap value determines the number of electron-hole pairs generated per photon. Therefore, reducing the bandgap results in more electron-hole pairs per absorbed photon, which leads to a lower dose of EUV resist.
[0122] Examples of materials used to prepare inorganic resins with an overall band gap of less than 3.5 eV are (the corresponding band gap values in eV are given in brackets): ZnO (3.2 eV), WO3 (3.2 eV), CdS (2.5 eV), CdSe (1.7 eV), GaP (2.25 eV), PdS (0.37 eV), etc.
[0123] When nanoparticles are used, the band gap can be widened due to quantum confinement effects (generally stronger for longer band gap materials).Thus, nanoparticles with diameters from 1 nm to 3 nm are expected to have a band gap of less than 3.5 eV.
[0124] In another embodiment, there is provided an inorganic resist composition comprising crosslinked nanoparticles. Resist compositions based on inorganic nanoparticles have been proposed in the art to increase EUV absorption. However, due to lack of threshold, such resists generally suffer from relatively low contrast and potentially also suffer from scum (i.e., the formation of residues in that part of the resist that should be developed away). Photons arriving at dark resist regions can induce inorganic nanoparticles to change their solubility because a single photon is sufficient to produce nanoparticle clusters.
[0125] Currently available chemically amplified resists suitable for EUV lithography have relatively low absorption characteristics, which leads to high dose levels required to mitigate the effects of photon shot noise (PSN). Most of the other known inorganic resist compositions are from the negative class, resulting in more heating of the projection optics. It is desirable to provide a method for making a positive photoresist suitable for EUV lithography. The inventors herein propose a method for making such a positive EUV photoresist by crosslinking inorganic nanoparticles during a post-application baking step and a step of breaking the crosslinks during EUV exposure. This allows positive highly absorbing resists while allowing tuning of the resist threshold to ensure improved lithography performance.
[0126] It is proposed herein to crosslink particles during the baking step by using a molecule susceptible to photon or electron-induced dissociation (i.e., having a function similar to that of a conventional photoacid generator (PAG)) as a ligand, which is bonded to a first group of inorganic nanoparticles (represented herein by particles A). The amount of the first group of inorganic nanoparticles A can be, for example, about half of the total amount of nanoparticles in the resist composition. The ligand is provided with one or more chemical groups that prevent the crosslinking of nanoparticles. The chemical group can be removed (destroyed) by heating during baking. Such a ligand will prevent the polymerization of nanoparticles in the resist solution used for spin coating.
[0127] The second set of inorganic particles (represented herein as particles B) can be chosen to have other weakly bonded ligands that can be displaced by the other side of the photons on the electron sensitive ligands on particles A during the baking step. This reaction will result in a cross-linked nanoparticle coating.
[0128] During lithographic exposure, photons from the electron-sensitive ligands of particle A will dissociate under the influence of EUV photons or low-energy electrons, leaving free nanoparticles in the exposed areas. These free nanoparticles can be removed during development.
[0129] Known nanoparticle-based resists change their solubility by changing the hydrophobicity of the particles or by the aggregation of nanoparticles / nanoclusters. However, the opposite approach is proposed herein, in which free nanoparticles are produced during lithographic exposure. The advantage of the positive composition proposed above is that changing the number of crosslinks per particle allows tuning the threshold of the number of photons on the electrons required to change the solubility of the particles, which is beneficial for resist contrast. Different resists can be used in different process steps, just as different EUV wavelengths and even non-EUV wavelengths can be used for less critical patterning steps in the overall device manufacturing process. The different resist types introduced above can be used in different process steps at EUV wavelengths to optimize the performance of individual processes and patterns being made.
[0130] In another embodiment, a resist composition is provided, which includes a substance including a self-assembling molecule having a self-assembling assembly group for self-assembly to a substrate material. The substrate can be a wafer substrate or another resist layer in contact with the layer of the resist composition above. The self-assembling molecule also has a passive end-capping group different from the self-assembling assembly group, which becomes an active end-capping group that can be combined with other chemical groups when utilizing lithography radiation such as EUV radiation. The resist composition further includes an inorganic nanoparticle that is configured to be not chemically bonded to the passive end-capping group or the self-assembling assembly group of the self-assembling molecule, wherein the inorganic nanoparticle is configured to be chemically bonded to the active end-capping group of the self-assembling molecule.
[0131] Such resist composition can form highly absorbed, ordered inorganic resist layer firmly attached to the surface (for example, wafer surface) of substrate.Such resist composition can have for example anisotropic acid diffusion or even do not have acid diffusion.Such resist layer can be designed to have less dosage, straighter profile, good etch resistance (because it is inorganic material) and owing to one or more better resolution in the following material properties: less pattern destruction, high mechanical strength of resist or the strong bonding to substrate surface.Resist layer can also be used for growing metal layer in z direction, to obtain the pattern with higher thickness.
[0132] Self-assembled monolayer (SAM) is a monolayer of functionalized molecules that can be prepared to passivate or functionalize the surface of a substrate. Such a monolayer is typically formed from a solution comprising dispersed functionalized self-assembled molecules or the gas phase of such a solution, resulting in deposition and bonding to a substrate of an ordered organic film with a thickness of about 2 nm.
[0133] Various types of nanoparticles are known in the literature.Metallic nanoparticles generally consist of a core comprising one or more types of metals having the desired phase, size, shape and crystallinity.
[0134] Typical metal nanoparticle (MNP) dispersions include nanoparticles dispersed in a solvent stabilized with a surfactant.Metallic nanoparticles can be deposited on a SAM-covered surface, for example by spin coating or dipping, thereby forming a disordered multilayer of nanoparticles.
[0135] The MNPs can be configured so as not to bind (not chemically attach) to SAM molecules having passive end-capping groups, such as passive carbon C group end-capped SAM molecules. An example of such a passive C end-capping group is -CH3.
[0136] MNPs can also be configured so that: when in such cases the SAM molecules have active endcaps (such as -COOH, -SH, etc.), there can be ligand exchange (i.e., chemical bonding) between MNP and MNP molecules. In such cases, surfactant molecules from the NMP surface can be replaced with active endcaps of SAM molecules.
[0137] The conversion of the passive capping groups into active capping groups of the SAM molecules may occur, for example, upon irradiation with photolithographic radiation, such as exposure with EUV radiation. In this way, the MNPs are anchored to the surface via the SAM molecules.
[0138] Azide (-N3) terminated SAMs can also be used to induce bonding to FePt-type MNPs, since azide is a group that can bond to C=C terminated surfactants at the MNPs. EUV radiation can induce such a reaction between -N3 and C=C groups.
[0139] It has also been shown that EUV photons or electrons generated upon absorption of EUV radiation by SAM molecules, by MNPs or by the substrate can in principle convert CH3 groups (or other passive end caps) into COOH groups (or other active end caps). Very low EUV doses can be sufficient to induce such local reactions.
[0140] In principle, it is also possible to use PAG-type molecules as SAM capping. In this way, the MNPs will form chemical bonds with the active capping SAM molecules via ligand exchange.
[0141] Several different routes of resist layer fabrication can be used. One approach is to form an EUV negative non-CAR MNP photoresist layer prepared by activation of a self-assembled monolayer by EUV radiation absorption, which enables activation of surface molecules. The active capping groups bind to the MNPs by a ligand exchange mechanism. Radiation absorption is increased due to the high radiation absorptivity of the MNPs. Secondary electrons can be generated at the MNPs, SAM layer, and substrate.
[0142] The MNPs are anchored to the surface covered by the active terminated end SAM. The SAM has EUV sensitive dissociated units in its chain. Upon EUV exposure, the EUV sensitive (e.g. containing sulfonate) molecules dissociate and the MNPs in the exposed areas become removable, while the MNPs in the unexposed areas remain anchored to the surface. In this way, the EUV layer acts as a positive non-chemically amplified resist (non-CAR).
[0143] Another approach is to use a surface covered with a SAM patterned by EUV radiation, where the MNPs are attached in a subsequent step. In such a case, the required radiation dose may be higher, however the electron blurring induced in the resist layer will be lower, which will result in a better defined pattern.
[0144] Another method is to use EUV radiation sensitive PAG class molecules as SAM end-capping. It has been shown that such molecules can be split into two parts (e.g., CFSO3- and TPS) during EUV exposure. In the absence of EUV activation, such EUV sensitive PAG class end-capping acts as a passive layer, and during activation and pattern definition by EUV radiation, the CFSO3-end-capping is maintained and the TPS part is detached. In addition, SAMs with -SH end-capping have been shown to have a higher affinity with inorganic nanoparticles than some other ligands for stable MNPs (such as -COOH end-capping SAM ligands, etc.).
[0145] MNP anchoring and cross-linking can occur upon exposure to EUV radiation. Cross-linking can be catalyzed, for example, by end-capping with the PAG fragment SbF6-SAM, and the surfactant end-capping is linked to the MNPs via an epoxy cross-linker.
[0146] PAG-type capping and epoxy crosslinking agents comprising an organic fullerene resist layer can form patterns upon EUV exposure due to cation-catalyzed crosslinking. Similar chemistry can be applied to MNPs as described above.
[0147] Chemically amplified negative nanoparticle EUV resists with anisotropic blur can be formed by loose assemblies formed by PAG-like capping, crosslinking agents, and rod-shaped MNPs on a SAM-covered surface, where MNP anchoring and crosslinking are induced upon EUV exposure. Crosslinking can be catalyzed by the PAG fragment SbF6-SAM capping, while surfactant capping can be linked to MNPs via epoxy crosslinking agents. Catalyst diffusion can be favored in the vertical direction.
[0148] MNPs with different shapes, including rod-like structures, have been reported in the literature. It has been shown that FePt nanoparticles can rotate and align under the influence of an external magnetic field. Such rod-shaped nanoparticles can become aligned in the vertical direction, and then the cationic catalyst diffusion is favored in the vertical direction, which will reduce the required dosage level.
[0149] Using any of the above mentioned methods, a MNP pattern can be produced, and the thickness of the MNP layer can be further increased, for example by using electroless metal deposition, in order to increase the etch resistance of the resist layer.
[0150] The use of the described resist in EUV lithography processes can be used in the manufacture of integrated circuits, as well as for other applications, such as in the manufacture of integrated optical systems, for magnetic domain memories, flat panel displays, liquid crystal displays (LCDs), guidance and detection patterns for thin film magnetic heads, and the like. It will be appreciated by those skilled in the art that in the context of such alternative applications, any use of the term "wafer" or "die" herein may be considered synonymous with the more general term "substrate" or "target portion", respectively. The substrate referred to herein may be processed before or after exposure in, for example, a track (a tool that typically applies a layer of resist to a substrate and develops the exposed resist), a measurement tool, and / or an inspection tool. In addition, the substrate may be processed more than once, for example to produce a multi-layer IC, so that the term substrate used herein may also refer to a substrate that already contains multiple processed layers.
[0151] Although specific embodiments of the present invention have been described above, it should be appreciated that the present invention can be put into practice in other ways except as described above. For example, resist compositions of the present invention can be used in patterning processes including resists comprising multiple layers to protect and / or enhance the invention. The above description is intended to be illustrative, rather than restrictive. Therefore it will be apparent to those skilled in the art that various modifications may be made to the present invention as described above without departing from the scope of the claims and clauses set forth below.
[0152] 1. A resist composition comprising an inorganic core-shell nanoparticle, the nanoparticle comprising a first material forming a core of the nanoparticle and a second material forming a shell around the core,
[0153] The second material has an energy band gap greater than an energy band gap of the first material.
[0154] 2. The resist composition of Clause 1, wherein the first material comprises CdSe and the second material comprises ZnS.
[0155] 3. The resist composition according to clause 1 or 2, wherein the nanoparticles are core-shell nanoparticles comprising a material selected from the group consisting of CdS / ZnS, CdSe / CdS and InAs / CdSe.
[0156] 4. A resist composition comprising an inorganic core-shell nanoparticle, the nanoparticle comprising a first material forming a core of the nanoparticle and a second material forming a shell around the core, wherein the absolute band gap position of the second material is arranged to shield one of electrons or holes as charge carriers and attract the other charge carrier.
[0157] 5. The resist composition of Clause 4, wherein the first material comprises ZnTe and the second material comprises CdSe.
[0158] 6. An anti-etching composition according to clause 4 or 5, wherein the band gap of the first material is higher than the band gap of the second material, characterized in that the absolute band gap positions of the first material and the second material are different on an absolute energy scale, thereby causing spatial separation of electrons and holes, wherein the holes are positioned closer to the surface of the core-shell nanoparticles.
[0159] 7. A resist composition comprising inorganic nanoparticles comprising a material having an overall band gap of less than 3.5 eV.
[0160] 8. The resist composition according to clause 7, wherein the material of the inorganic particles is selected from the list consisting of ZnO, WO3, CdS, CdSe, GaP, InAs, InP, GaAs, CdTe, GaSb, InN, InSb, ZnSe and ZnTe.
[0161] 9. A resist composition for positive photoresist, comprising a first group of inorganic nanoparticles A and a second group of inorganic nanoparticles B,
[0162] wherein nanoparticle A is provided with photons on an electron sensitive ligand, the electron sensitive ligand comprising a chemical group having a first side attached to the nanoparticle A and a second side arranged to prevent cross-linking of the nanoparticles A and B at room temperature, and the chemical group is removable at a temperature above the room temperature;
[0163] wherein nanoparticle B is provided with a ligand having a weakly bonded chemical group arranged to be displaceable by said second side of said chemical group at a temperature above room temperature by photons attached to said electron sensitive ligand of nanoparticle A, thereby providing cross-linking of nanoparticles A and B; and
[0164] Wherein the photons on the electron sensitive ligand are arranged to dissociate from the nanoparticle A during lithographic exposure with photons or low energy photons.
[0165] 10. The resist composition according to Clause 9, wherein the amount of the inorganic nanoparticles A is about half of the total amount of the inorganic nanoparticles A and B.
[0166] 11. The resist composition of clause 9, wherein the nanoparticles comprise photons on electron sensitive ligands and the dissociation during photolithographic exposure provides free nanoparticles that can be removed by a resist developer.
[0167] 12. A method for preparing a resist composition for positive photoresist, the resist composition comprising a first group of inorganic nanoparticles A and a second group of inorganic nanoparticles B, the method comprising the following steps:
[0168] Providing a first group of nanoparticles A with photons on an electron-sensitive ligand, the electron-sensitive ligand comprising a chemical group having a first side attached to the nanoparticle A and a second side arranged to prevent cross-linking of the nanoparticles A and B at room temperature, the chemical group being removable at a temperature above the room temperature; and wherein the photons on the electron-sensitive ligand are arranged to dissociate from the nanoparticle A during lithographic exposure with photons or low-energy photons; and
[0169] The second set of nanoparticles B are provided with ligands having weakly bound chemical groups arranged to be displaceable by photons attached to the electron sensitive ligands of nanoparticle A at temperatures above room temperature from the second side of the chemical group.
[0170] 13. The method according to clause 12, comprising the further step of applying a baking temperature to the positive photoresist to allow cross-linking of the nanoparticles A and B.
[0171] 14. The method according to clause 13 comprises a further step in which the cross-linked positive photoresist is exposed to photons or low-energy photons so that the photons on the electron sensitive ligand dissociate from the nanoparticles A during the photolithographic exposure, thereby leaving free nanoparticles in the exposed areas of the positive photoresist.
[0172] 15. A resist composition comprising
[0173] a substance comprising self-assembling molecules having self-assembling assembling body groups for self-assembly to a substrate material, the substrate contacting the layer of the resist composition,
[0174] The self-assembling molecule also has a passive capping group different from the self-assembling assembly group, the passive capping group becoming a reactive capping group when irradiated with photolithographic radiation; and
[0175] an inorganic nanoparticle configured not to chemically bind to the passive end-capping group of the self-assembling molecule or the self-assembling assembly group,
[0176] The inorganic nanoparticles are configured to chemically bond with the active capping groups of the self-assembling molecules.
[0177] 16. The resist composition according to Clause 15, wherein the resist composition has anisotropic acid diffusion or no acid diffusion property.
[0178] 17. The resist composition according to clause 15 or 16, comprising multiple layers of inorganic nanoparticles.
[0179] 18. The resist composition according to any one of Clauses 15 to 17, wherein the inorganic nanoparticles are metal nanoparticles.
[0180] 19. The resist composition according to any one of clauses 15 to 18, wherein the passive capping group is a C capping group that can be converted into the active capping group when exposed to the photolithographic radiation beam, such as a -CH3 capping group.
[0181] 20. The resist composition according to any one of Clauses 15 to 19, wherein the reactive end-capping groups of the self-assembled monolayer molecules are selected from -COOH, -SH or -N3 groups.
[0182] 21. The resist composition according to any one of clauses 15 to 20, wherein the reactive end capping groups of the self-assembled monolayer molecules are PAG end capping groups comprising one or more of the groups CFSO3-, TPS or SbF6.
[0183] 22. An anti-etching composition according to clause 21, wherein the passive capping group is a PAG group comprising a CFSO3- and a TPS group, and the passive capping group is activated by the dissociation of the TPS group when irradiated with photolithography radiation, so that the CFSO3- group forms the active capping group.
[0184] 23. A resist composition according to clause 22, wherein upon irradiation with photolithographic radiation, the inorganic particles attached to the self-assembling molecules become removable at the irradiated areas of the resist layer, while the inorganic particles from the unirradiated areas remain bonded in the resist layer.
[0185] 24. The resist composition according to any one of Clauses 15 to 20, wherein the reactive end-capping groups of the self-assembled monolayer molecules are -N3 azide groups and the inorganic nanoparticles comprise FePt.
[0186] 25. The resist composition according to any one of Clauses 15 to 24, wherein the inorganic particles are rod-like elongated particles.
[0187] 26. The resist composition of clause 25, wherein the catalyst diffusion is oriented substantially in a direction perpendicular to the substrate, thereby providing a resist layer having anisotropic haze, the layer of the inorganic resist composition being in contact with the substrate.
[0188] 27. The resist composition of any one of Clauses 15 to 26, wherein the surface of the inorganic nanoparticles is protected with a surfactant having C=C endcaps linked to the inorganic nanoparticles via epoxy crosslinker groups.
[0189] 28. The resist composition according to any one of Clauses 15 to 27, wherein the photolithographic radiation used to transform the passive capping groups into active capping groups is EUV radiation.
[0190] 29. A substrate coated with a layer of a resist composition according to any one of Clauses 1 to 11 and Clauses 15 to 28.
Claims
1. A resist composition comprising a substance comprising a plurality of self-assembling molecules, each of the self-assembling molecules having a self-assembling body group for self-assembly to a substrate material contacting a layer of the resist composition, The self-assembling molecule further has a passive end-capping group different from the self-assembling assembly group, wherein the passive end-capping group comprises a C end-capping group or an azide end-capping group, and the passive end-capping group becomes an active end-capping group when irradiated with photolithographic radiation; and A plurality of rod-shaped long inorganic nanoparticles are configured not to be chemically bonded to the passive end-capping groups of the self-assembling molecules or the self-assembling assembly groups, wherein the inorganic nanoparticles are configured to be chemically bonded to the active end-capping groups of the self-assembling molecules, and wherein in the case where the passive capping group is the C capping group, the C capping group comprises a -CH3 capping group which is convertible into the reactive capping group upon exposure to the photolithographic radiation beam, wherein the reactive capping group comprises -COOH, and In the case where the passive capping group is the azide capping group, the surface of the inorganic nanoparticle is protected with a surfactant having a C=C endcapping group linked to the inorganic nanoparticle via an epoxy crosslinker group, wherein the azide capping group becomes the active capping group capable of reacting with the surfactant having the C=C endcapping group when irradiated with the photolithographic radiation. 2 . The resist composition according to claim 1 , wherein the resist composition has anisotropic acid diffusion or no acid diffusion property.
3. The resist composition according to claim 1 or 2, comprising multiple layers of inorganic nanoparticles. 4 . The resist composition according to claim 1 , wherein the inorganic nanoparticles are metal nanoparticles.
5. The resist composition of claim 1, wherein catalyst diffusion is oriented substantially in a direction perpendicular to the substrate, thereby providing a resist layer having anisotropic haze, the layer of the resist composition being in contact with the substrate.
6. The resist composition according to any one of claims 1 to 2, wherein the photolithographic radiation used to transform the passive capping groups into active capping groups is EUV radiation.
7. A substrate coated with a layer of the resist composition according to any one of claims 1 to 6.
Citation Information
Patent Citations
Irradiation-assisted immobilization and patterning of nanostructured materials on substrates for device fabrication
US20040203256A1
Radiation sensitive self-assembled monolayers and uses thereof
US20070278179A1